Gambaran Pengetahuan Ibu Teantang Diare Pada Balita di Desa Sibarani Nasampulu Kecamatan Lagboti Tahun 2022 - Indra Hizkia P; Christin Sitinjak (Poltekkes Kemenkes Medan, 2022)
Diarrhea is loose or liquid bowel movements with a frequency of 3 or more times per day which can be caused by various infectious agents such as bacteria, viruses, and parasites. Infection can be spread from contaminated food and poor hygiene. In 2017, the incidence of diarrheal disease increased to 574/1000. In general, those who are most often noted for experiencing diarrhea are small children such as toddlers, especially children who cannot express their complaints. Therefore, mothers who interact with children the most must have knowledge of diarrheal diseases so that they can prevent further complications. This study aims to determine the picture of Mother's Knowledge About Diarrhea in Toddlers in Sibarani Nasampulu Village, Laguboti District in 2022. The method used in this research uses descriptive methods and sampling techniques which are carried out with total sampling technique, namely the number of respondents of mothers under five in Sibarani Nasampulu Village totaling 46 respondents. The research instrument used a questionnaire about maternal knowledge about diarrhea. The results of the research showed that there were 39 people with